Measuring MENA Islamic bank efficiency: Does country income level have an impact? - Mohammad Noor, Mohammad Akbar Noor; Ahmad, Nor Hayati (2011)
Islamic banks today exist in all parts of the world, and are looked upon as a viable alternative system which has many things to offer.While it was initially developed to fulfill the needs of Muslims,Islamic banking has now gained universal acceptance.Islamic banking is recognized as one of the fastest growing areas in banking and finance.Since the opening of the first Islamic bank in Egypt in 1963, Islamic banking has grown rapidly all over the world. So in comparison, Islamic banking is relatively new phenomenon as the first Islamic bank, Mit Gharm Local Savings Bank of Egypt, was only established in 1963.Even then, the real growth of Islamic finance did not begin until the 1980s when Middle East countries experienced a large growth in surplus funds.Since then Muslim investment has spread throughout Europe and Asia, and Islamic finance is still expanding. Direct Islamic financing methods, such as with Islamic bonds, are gaining popularity in the West as is Islamic based funds management.The number of Islamic financial institutions worldwide has risen to over 300 today in more than 75 countries concentrated mainly in the Middle East and Southeast Asia (with Bahrain and Malaysia the biggest hubs), but are also appearing in Europe and the United States.The Islamic banking total assets worldwide are estimated to have exceed $250 billion and are growing at an estimated pace of 15 percent a year.Zaher and Hassan (2001) suggested that Islamic banks are set to control some 40-50 percent of Muslim savings by 2009/10.Saleh and Zaitun (2007) found that interesting development of Islamic banking globally.This sector has not only grown in the Muslim world, but has also gained significant attention in the Western world, with over 250 Islamic banks worldwide controlling approximately US$400 billion in assets and client money.The growth of these banks is proof of their success, and an indication that these banks continue to grow in number and size worldwide.